Latent Profile Analysis of the Five Facet Mindfulness Questionnaire in a Sample With a History of Recurrent Depression. (January 2020) - Gu, Jenny; Karl, Anke; Baer, Ruth; Strauss, Clara; Barnhofer, Thorsten; Crane, Catherine
Extending previous research, we applied latent profile analysis in a sample of adults with a history of recurrent depression to identify subgroups with distinct response profiles on the Five Facet Mindfulness Questionnaire and understand how these relate to psychological functioning. The sample was randomly divided into two subsamples to first examine the optimal number of latent profiles (test sample; n = 343) and then validate the identified solution (validation sample; n = 340). In both test and validation samples, a four-profile solution was revealed where two profiles mapped broadly onto those previously identified in nonclinical samples: "high mindfulness" and "nonjudgmentally aware." Two additional subgroups, "moderate mindfulness" and "very low mindfulness, " were observed. "High mindfulness" was associated with the most adaptive psychological functioning and "very low mindfulness" with the least adaptive. In most people with recurrent depression, mindfulness skills are expressed evenly across different domains. However, in a small minority a meaningful and replicable uneven profile indicating nonjudgmental awareness is observable. Current findings require replication and future research should examine the extent to which profiles change from periods of wellness to illness in people with recurrent depression and how profiles are influenced by exposure to mindfulness-based intervention.